DOMESTIC ADMINISTRATIVE-DELICT LEGISLATION ON THE WAY TO ITS IMPROVEMENT - Гончарук, Степан Тихонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article explores some issues of further improvement of domestic administrative and tort legislation. Research methods: system analysis and synthesis, comparative legal and doctrinal cognition. Results: some problems of further improvement of the administrative-tort legislation of Ukraine are identified and the ways of their solution are suggested. Discussion: the need for a radical reform of the domestic administrative-tort legislation in the context of European integration of the Ukrainian state. The article is devoted to the research of the further improvement of the administrative-delict legislation of Ukraine. It is noted that, along with the need for a radical and fundamental reform of the contents of such legislation, which is expected in an indefinite perspective, today it also requires less costly, not time-consuming so-called «cosmetic» improvement. Issues that are fundamentally new and are consequences of systematic changes of the modern administrative-delict legislation, which require their urgent solution, include those that are connected, in particular, with the establishment of administrative liability of legal entities, the determination of a system of administrative penalties that can be applied to such subjects, and procedural particularities of their application; with the possibility of adoption the Code of Criminal Misconducts, which will undoubtedly include some of the most socially dangerous administrative misconducts, etc. However, nowadays the less important improvements of the current Code on Administrative Offences are important. It is necessary to clarify certain definitions, provisions, terms, redaction of separate articles of this Code of both substantive and procedural contents. Such revision concerns the improvement of certain definitions and concepts, the exclusion of separate acts (so-called «dead» articles) from the category of administrative-punishable offences, the determination of administrative liability for certain unlawful acts, the prediction of the peculiarities of the administrative liability of certain subjects, in particular people’s deputies and members of local councils, judges; clarification of certain procedural time limits, etc. The exclusion of the mentioned deficiencies will help to improve the qualification of certain unlawful acts, strengthen the law and order in the country, improve the current legislation on administrative offences and its applying.